(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2019)
Peer assessment has attracted more attention an effective assessment tool in recent years. Peer assessment refers to the arrangement for peers to consider the quality of learning outcomes of others of similar status, it received attention of various studies due to the growing interest in the student centered approach as learners need to be involved in the learning process even in the assessment. This paper is a critical review of previous studies on peer assessment in English as Second/Foreign Language (ESL/EFL) context. Fifteen peer assessment studies from 2004 to 2017 were extensively reviewed and systematically analyzed. Peer assessment of the reviewed studies were on the quality of the writing outcomes of students in the EFL/ESL contexts, as writing skill occupies an important role in teaching English language. As a critical review paper of these studies, this paper highlights practical use of peer assessment and the important challenges or issues that need to be considered when utilizing peer assessment in the classroom. This paper hopes that practical measures of peer assessment will be utilized effectively by educators in the ESL and EFL classrooms in the near future.